Laminated foil for aluminum electrolytic capacitor, preparation method of laminated foil and aluminum electrolytic capacitor

By designing asymmetric cracks with a depth less than the thickness of the sintered layer on the sintered layer of the accumulated foil, and combining the pulling and sintering treatment, the problems of fracture and corrosion of the accumulated foil during the cutting process are solved, and higher flexural strength and plasticity are achieved.

CN119889932AActive Publication Date: 2025-04-25ULANQAB DONGGUANGYANG ELECTRONIC MATERIALS TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411994431.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

The existing accumulated foil is prone to cracking and breaking the foil during the cutting process, and the crack depth of the sintered layer is too large, which destroys the material continuity, resulting in poor bending strength and corrosion problems.

Method used

A laminated foil with an aluminum sintered layer is used, and there are multiple cracks on the sintered layer, the crack depth is smaller than the thickness of the sintered layer, and the cracks are distributed asymmetrically. The bending strength and plasticity of the foil are enhanced by pulling and sintering treatment.

Benefits of technology

It improves the bending strength and plasticity of the accumulated foil, reduces the risk of fracture during cutting, and avoids substrate corrosion, and improves the reliability of capacitor production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119889932A_ABST
    Figure CN119889932A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of electrode materials, and particularly relates to a laminated foil for an aluminum electrolytic capacitor and a preparation method thereof and the aluminum electrolytic capacitor, the laminated foil for the aluminum electrolytic capacitor comprises a base material and a sintered layer which is arranged on the surface of at least one side of the base material and composed of an aluminum sintered body, and the sintered layer on each side is provided with a plurality of cracks. In the thickness direction of the sintered layer, the multiple cracks independently extend from the surface of the side, away from the base material, of the sintered layer to the surface of the base material, and the depth of the cracks is smaller than the thickness of the sintered layer. The depth of the crack in the laminated foil does not reach the surface of the base material, the continuity of the material is not damaged, and the bending strength and plasticity of the laminated foil are improved, so that the stress cannot be concentrated at one point to be released in the winding and cutting processes of the foil roll, the risk of breakage during cutting is reduced, and meanwhile, the phenomenon that a bath solution is immersed into the surface of the base material in the formation process is avoided; therefore, the corrosion to the base material is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrode materials, and in particular relates to a laminated foil for an aluminum electrolytic capacitor, a preparation method thereof, and an aluminum electrolytic capacitor. Background Art

[0002] Since the 1990s, with the continuous development of electronic information technology and the expansion of its application fields, aluminum electrolytic capacitors have continued to develop towards miniaturization, high performance and high reliability.

[0003] Laminated foil is a kind of electrode foil, the core raw material of capacitors. Its specific surface area is 25% to 35% larger than that of traditional etched foil, and its production process is pollution-free. In the future, it will gradually replace most of the traditional etched foils, and its development prospects are broad. However, the strength of laminated foil is poor at present, and it is easy to crack and break the foil and produce burrs during the cutting process, which brings great difficulties to the production of capacitors. Summary of the invention

[0004] The main purpose of the present invention is to provide a laminated foil for aluminum electrolytic capacitors, a preparation method thereof, and an aluminum electrolytic capacitor. The depth of the cracks in the laminated foil of the present invention does not reach the surface of the substrate, does not damage the continuity of the material, improves the bending strength and plasticity of the laminated foil, so that the stress of the foil roll will not be concentrated at one point during the winding and cutting process, reduces the risk of breakage during cutting, and prevents the bath liquid from penetrating into the surface of the substrate during the formation process, thereby reducing corrosion to the substrate.

[0005] In order to achieve the above objectives, the present invention provides the following technical solutions.

[0006] A first aspect of the present invention provides a laminated foil for an aluminum electrolytic capacitor, comprising a substrate and a sintered layer composed of an aluminum sintered body on at least one side surface of the substrate, wherein the sintered layer on each side has a plurality of cracks, and along the thickness direction of the sintered layer, the plurality of cracks independently extend from a side surface of the sintered layer away from the substrate to a surface of the substrate, and the depth of the cracks is less than the thickness of the sintered layer.

[0007] In some embodiments of the present invention, the sintered layers are provided on two opposite side surfaces of the substrate; based on the substrate, a plurality of cracks in the sintered layers on two sides are independently and asymmetrically distributed.

[0008] In some embodiments of the present invention, based on the sintered layer on one side, the plurality of cracks are arranged at intervals along the length direction of the sintered layer.

[0009] In some embodiments of the present invention, based on the sintered layer on one side, the intervals between two adjacent cracks are independently 50 μm to 350 μm.

[0010] In some embodiments of the present invention, based on the sintered layer on one side, the intervals between two adjacent cracks are independently 100 μm to 320 μm.

[0011] In some embodiments of the present invention, based on the sintered layer on one side, the intervals between two adjacent cracks are independently 100 μm to 300 μm.

[0012] In some embodiments of the present invention, based on the sintered layer on one side, the intervals between two adjacent cracks are independently 100 μm to 250 μm.

[0013] In some embodiments of the present invention, the plurality of cracks in the sintered layer located at both sides are alternately distributed along the length direction of the sintered layer.

[0014] In some embodiments of the present invention, the width of each crack along the length direction of the sintered layer is independently 0.1 μm to 5 μm.

[0015] In some embodiments of the present invention, the depth of the cracks is independently less than or equal to 95% of the thickness of the sintered layer.

[0016] In some embodiments of the present invention, the depth of the cracks is independently 40% to 95% of the thickness of the sintered layer.

[0017] In some embodiments of the present invention, the depth of the cracks is independently 50% to 95% of the thickness of the sintered layer.

[0018] In some embodiments of the present invention, the thickness of the sintered layer on each side is independently 45 μm to 200 μm.

[0019] In some embodiments of the present invention, the thickness of the substrate is 10 μm to 50 μm.

[0020] In some embodiments of the present invention, the substrate is selected from aluminum foil.

[0021] The second aspect of the present invention provides a method for preparing the laminated foil for aluminum electrolytic capacitors described in the first aspect, the preparation method comprising: coating a slurry prepared with aluminum powder as raw material on at least one side surface of a substrate, and sequentially performing drying treatment, straightening treatment and sintering treatment to obtain the laminated foil for aluminum electrolytic capacitors.

[0022] In some embodiments of the present invention, the straightening treatment includes: passing the foil roll obtained after the drying treatment through a roller at a uniform speed under the tension of the roller. A roller is a mechanical element that transmits force by rotation, is generally cylindrical, and is often made of metal, rubber, and other materials.

[0023] In some embodiments of the present invention, the diameter of the roller is 3 mm to 20 mm.

[0024] In some embodiments of the present invention, the tension of the roller is 5kg to 50kg.

[0025] In some embodiments of the present invention, the number of passes is 1 to 5 times.

[0026] In some embodiments of the present invention, the foil roll passes through the roller at an angle of 90° to 180°.

[0027] In some embodiments of the present invention, the temperature of the drying treatment is 30° C. to 100° C., and the time of the drying treatment is 1 min to 30 min.

[0028] In some embodiments of the present invention, the particle size D50 of the aluminum powder is 1 μm to 10 μm.

[0029] In some embodiments of the present invention, the particle size D50 of the aluminum powder is 3 μm to 5 μm.

[0030] In some embodiments of the present invention, the sintering temperature is 560° C. to 650° C., and the sintering time is 2 h to 20 h.

[0031] A third aspect of the present invention provides an aluminum electrolytic capacitor, which includes the laminated foil for an aluminum electrolytic capacitor described in the first aspect or the laminated foil for an aluminum electrolytic capacitor produced by the production method described in the second aspect.

[0032] Compared with the prior art, the present invention achieves the following technical effects:

[0033] The crack depth in the sintered layer of the laminated foil of the present invention does not reach the surface of the substrate, and does not damage the continuity of the material, thereby improving the bending strength and plasticity of the laminated foil, so that the stress of the foil roll will not be concentrated and released at one point during the winding and cutting process, reducing the risk of breakage during cutting, and preventing the bath liquid from penetrating into the surface of the substrate during the formation process, thereby reducing corrosion to the substrate.

[0034] In the present invention, asymmetrically distributed cracks exist in the sintered layer of the laminated foil, which can further improve the bending strength of the laminated foil and enhance the plasticity of the material.

[0035] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention, it can be implemented according to the contents of the specification. In order to make the above and other purposes, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Various other advantages and benefits will become apparent to those skilled in the art by reading the detailed description of the preferred embodiments below. The accompanying drawings are only used for the purpose of illustrating the preferred embodiments and are not to be considered as limiting the present invention. In the accompanying drawings:

[0037] Figure 1 A schematic cross-sectional view of a laminated foil for an aluminum electrolytic capacitor according to some embodiments of the present invention;

[0038] Figure 2 4 is a cross-sectional view of a laminated foil for an aluminum electrolytic capacitor prepared in Example 1 of the present invention;

[0039] Figure 3 2 is a cross-sectional view of a laminated foil for an aluminum electrolytic capacitor prepared in Example 2 of the present invention;

[0040] Figure 4 This is a cross-sectional view of the laminated foil for aluminum electrolytic capacitor produced in Comparative Example 1 of the present invention.

[0041] Reference numerals

[0042] 100. Laminated foil;

[0043] 10. Base material; 20. Sintered layer; 21. Crack. DETAILED DESCRIPTION

[0044] The exemplary embodiments of the present invention will be described in more detail below with reference to specific embodiments. It should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the specification and claims of the present invention and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0046] In the description of the embodiments of the present invention, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.

[0047] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0048] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B may represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this document generally indicates that the associated objects before and after are in an "or" relationship.

[0049] In the description of the embodiments of the present invention, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0050] In the description of the embodiments of the present invention, the technical terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise", "axial", "radial", "circumferential", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present invention and simplifying the description, and do not indicate or imply that the referred device or element must have a specific orientation, be constructed and operated in a specific orientation, and therefore should not be understood as limiting the embodiments of the present invention.

[0051] In the description of the embodiments of the present invention, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the embodiments of the present invention can be understood according to specific circumstances.

[0052] The existing laminated foil has poor bending strength, stress concentration during cutting, easy cracking and breaking of the foil, and many burrs are generated during cutting, which brings great difficulties to the production of capacitors.

[0053] In addition, in the prior art, most of the cracks in the cross section of the sintered layer are distributed symmetrically, and the crack depth will penetrate into the substrate. The cracks at the symmetrical locations destroy the continuity of the material, resulting in the weakest mechanical properties of the material at this location. In subsequent processing processes, such as chemical formation, cutting, and winding, corrosion, breakage, and other adverse conditions are prone to occur.

[0054] The present invention provides a laminated foil for an aluminum electrolytic capacitor, see Figure 1 As shown, the laminated foil 100 includes a substrate 10 and a sintered layer 20 composed of an aluminum sintered body on at least one side surface of the substrate 10, and the sintered layer 20 on each side has a plurality of cracks 21. Along the thickness direction of the sintered layer 20, the plurality of cracks 21 independently extend from the side surface of the sintered layer 20 away from the substrate 10 to the surface of the substrate 10, and the depth of the crack 21 is less than the thickness of the sintered layer 20.

[0055] In the embodiment of the present invention, a sintered layer 20 is provided on one side of the substrate 10, i.e., a single side, or on two opposite sides of the substrate 10, i.e., both sides. The sintered layer 20 is composed of an aluminum sintered body, and the sintered layer 20 on each side has a plurality of cracks 21. Figure 1 As shown, along the thickness direction of the sintered layer 20, the crack 21 extends from the side surface of the sintered layer 20 away from the substrate 10 to the surface of the substrate 10, and the depth of the crack 21 is less than the thickness of the sintered layer 20, so that the crack depth on the sintered layer 20 does not reach the surface of the substrate 10, and does not damage the continuity of the material, thereby improving the bending strength and plasticity of the laminated foil, so that the stress of the foil roll will not be concentrated at one point during the winding and cutting process, reducing the risk of the foil roll breaking, and preventing the bath liquid from penetrating into the surface of the substrate 10 during the chemical formation process, thereby reducing corrosion to the substrate 10.

[0056] Continue to see Figure 1 As shown, the sintered layer 20 located on any side of the substrate 10 has a plurality of cracks 21 , and the plurality of cracks 21 independently extend along the thickness direction of the sintered layer 20 , and the extension depth is less than the thickness of the sintered layer 20 .

[0057] In some embodiments of the present invention, the depth H of the crack 21 is independently less than or equal to 95% of the thickness of the sintered layer 20, further reducing the breakage of the foil roll and reducing the corrosion of the bath liquid to the substrate 10. The depth H of the crack 21 provided by the present invention can be independently 40% to 95% of the thickness of the sintered layer 20; preferably, the depth H of the crack 21 is independently 50% to 95% of the thickness of the sintered layer 20. Exemplarily, the depth H of the crack 21 can be 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, 93%, 94%, 95% of the thickness of the sintered layer 20 or any value that meets the above range.

[0058] In some embodiments of the present invention, during the straightening and sintering processes, a small number of cracks 21 have a depth H that reaches the surface of the aluminum foil. In the present invention, the depth H of the crack 21 reaches the surface of the aluminum foil at a ratio of less than 5%. Exemplarily, the depth H of the crack 21 reaches the surface of the aluminum foil at a ratio of 1%, 2%, 3%, 4%, or any value that satisfies the above range. That is, the depth H of the crack 21 that does not reach the surface of the aluminum foil is greater than or equal to 95%. Exemplarily, the depth H of the crack 21 that does not reach the surface of the aluminum foil is 95%, 96%, 97%, 98%, 99%, 100%, or any value that satisfies the above range.

[0059] In some embodiments of the present invention, the width L of each crack 21 along the length direction of the sintered layer 20 is independently 0.1 μm to 5 μm. The width L of the crack 21 provided by the present invention can be a value in the range composed of any two values ​​in the above range, for example, it can be 0.1 μm to 1.5 μm, 1.5 μm to 3 μm, 3 μm to 5 μm, and so on. The width L of the crack 21 provided by the present invention can also be one of 0.1μm, 0.2μm, 0.4μm, 0.5μm, 0.6μm, 0.8μm, 1.0μm, 1.2μm, 1.4μm, 1.5μm, 1.6μm, 1.8μm, 2.0μm, 2.2μm, 2.4μm, 2.5μm, 2.6μm, 2.8μm, 3.0μm, 3.2μm, 3.4μm, 3.5μm, 3.6μm, 3.8μm, 4.0μm, 4.2μm, 4.4μm, 4.5μm, 4.6μm, 4.8μm, 5.0μm or any value that meets the above range.

[0060] Continue to see Figure 1As shown, for the sintered layer 20 on either side of the substrate 10 , that is, for the sintered layer 20 on one side, a plurality of cracks 21 are arranged at intervals along the length direction of the sintered layer 20 .

[0061] In some embodiments of the present invention, for a single-sided sintered layer 20, the spacing D between two adjacent cracks 21 may be independently 50 μm to 350 μm. The spacing D between two adjacent cracks 21 provided by the present invention may be a value in the interval consisting of any two values ​​in the above interval, for example, 50 μm to 200 μm, 100 μm to 350 μm, 100 μm to 300 μm, 200 μm to 280 μm, 280 μm to 350 μm, and so on. The spacing between two adjacent cracks 21 provided by the present invention can also be one of 50μm, 60μm, 70μm, 80μm, 90μm, 100μm, 110μm, 120μm, 130μm, 140μm, 150μm, 160μm, 170μm, 180μm, 190μm, 200μm, 210μm, 220μm, 230μm, 240μm, 250μm, 260μm, 270μm, 280μm, 290μm, 300μm, 310μm, 320μm, 330μm, 340μm, 350μm or any value that meets the above range.

[0062] Continue to see Figure 1 As shown, the two opposite surfaces of the substrate 10, that is, both sides of the substrate 10, have sintered layers 20, and based on the substrate 10, a plurality of cracks 21 of the sintered layers 20 on both sides are independently and asymmetrically distributed.

[0063] In an embodiment of the present invention, the multiple cracks 21 in the sintered layer 20 located on the A side of the substrate and the multiple cracks 21 in the sintered layer 20 located on the B side of the substrate are independently distributed asymmetrically, and the depth H of the cracks 21 does not reach the surface of the substrate 10, and does not damage the continuity of the material, thereby further improving the bending strength and plasticity of the laminated foil. During the winding and cutting process of the foil roll, the stress will not be concentrated at one point for release, reducing the risk of the foil roll breaking, and at the same time avoiding the bath liquid from penetrating into the surface of the substrate 10 during the chemical formation process, thereby reducing corrosion to the substrate 10.

[0064] In some embodiments of the present invention, the multiple cracks 21 of the sintered layers 20 located on both sides are alternately distributed along the length direction of the sintered layer 20. It can be understood that the multiple cracks 21 in the sintered layer 20 located on the A side of the substrate and the multiple cracks 21 in the sintered layer 20 located on the B side of the substrate are alternately arranged along the length direction of the sintered layer 20, further improving the bending strength of the laminated foil and improving the plasticity of the material.

[0065] In the embodiment of the present invention, for the sintered layer 20 on any side of the substrate 10, that is, for the sintered layer 20 on each side, the thickness of the sintered layer 20 can be 45 μm to 200 μm independently. The thickness of the sintered layer 20 provided by the present invention can be a value in the range composed of any two values ​​in the above range, for example, it can be 45 μm to 60 μm, it can be 60 μm to 75 μm, it can also be 75 μm to 100 μm, it can also be 100 μm to 200 μm, and so on. The thickness of the sintered layer 20 provided by the present invention can also be 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, 105μm, 110μm, 115μm, 120μm, 125μm, 130μm, 135μm, 140μm, 145μm, 150μm, 155μm, 160μm, 165μm, 170μm, 175μm, 180μm, 185μm, 190μm, 195μm, 200μm or any value satisfying the above range.

[0066] In an embodiment of the present invention, the thickness of the substrate 10 may be 10 μm to 50 μm. The thickness of the substrate 10 provided by the present invention may be a value of an interval consisting of any two values ​​within the above range, for example, it may be 10 μm to 30 μm, or 30 μm to 50 μm, and so on. The thickness of the substrate 10 provided by the present invention may also be one of 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, or any value satisfying the above range.

[0067] In the embodiment of the present invention, the substrate 10 may be a substrate used as a laminate foil for an aluminum electrolytic capacitor, for example, a substrate known in the art may be used.

[0068] In some embodiments of the present invention, the substrate 10 may be selected from aluminum foil of pure aluminum or aluminum alloy.

[0069] The present invention also provides a method for preparing a laminated foil for an aluminum electrolytic capacitor. The key is to perform a stretching and straightening treatment on the substrate coated with the slurry before the sintering treatment, thereby improving the bending strength and plasticity of the laminated foil, and ensuring that the stress is not concentrated at one point during the winding and cutting process of the foil roll, thereby reducing the risk of the foil roll breaking, and at the same time avoiding the bath liquid from penetrating into the surface of the substrate during the formation process, thereby reducing corrosion to the substrate.

[0070] The method for preparing the laminated foil for aluminum electrolytic capacitors of the present invention is carried out according to the following steps.

[0071] (1) Prepare slurry using aluminum powder as raw material.

[0072] In an embodiment of the present invention, aluminum powder is added into colloid and mixed evenly to prepare slurry.

[0073] In some embodiments of the present invention, the colloid may be colloid A formed by a solvent and a crosslinking agent A, colloid B formed by a solvent and a crosslinking agent B, or a mixed colloid formed by a solvent and the crosslinking agents A and B.

[0074] In some embodiments of the present invention, the solvent is not particularly limited and may be one or more of water, ethanol, toluene, and acetone.

[0075] In some embodiments of the present invention, the crosslinking agent A is not particularly limited, and one or more of natural resins, organic substances, inorganic substances, etc. can be used appropriately. Specifically, the crosslinking agent A can be one or more of epoxy resin, polyurethane, acrylic resin, and phthalic anhydride.

[0076] In some embodiments of the present invention, the crosslinking agent B is not particularly limited, and one or more of natural resins, organic substances, inorganic substances, etc. can be used appropriately. Specifically, the crosslinking agent B can be one or more of epoxy resin, polyurethane, acrylic resin, and phthalic anhydride.

[0077] In some embodiments of the present invention, a mixed glue formed by a solvent, a crosslinking agent A and a crosslinking agent B is used.

[0078] In some embodiments of the present invention, crosslinking agent A and crosslinking agent B may be the same or different.

[0079] In some embodiments of the present invention, in colloid A, the mass percentage of crosslinking agent A is 5% to 30%. The mass percentage of crosslinking agent A in colloid A provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 5% to 15%, or 15% to 30%, and so on. The mass percentage of crosslinking agent A in colloid A provided by the present invention can also be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% or any value that meets the above range value.

[0080] In some embodiments of the present invention, in colloid B, the mass percentage of crosslinking agent B is 5% to 30%. The mass percentage of crosslinking agent B in colloid B provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 5% to 15%, or 15% to 30%, and so on. The mass percentage of crosslinking agent B in colloid B provided by the present invention can also be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, 30% or any value that meets the above range value.

[0081] In some embodiments of the present invention, the mixed glue can be prepared by first preparing colloid A and colloid B separately and then mixing colloid A and colloid B; or by mixing crosslinking agent A and crosslinking agent B to prepare the mixed glue.

[0082] In some embodiments of the present invention, the mass of the mixed glue is 5% to 20% of the mass of the aluminum powder. The mass of the mixed glue provided by the present invention is the mass of the aluminum powder in the interval composed of any two values ​​in the above interval, for example, it can be 5% to 10%, it can be 10% to 15%, it can also be 15% to 20%, and so on. The mass of the aluminum mixed glue provided by the present invention is one of 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20% of the mass of the aluminum powder or any ratio that satisfies the above range.

[0083] In some embodiments of the present invention, the particle size D50 of the aluminum powder may be 1 μm to 10 μm; preferably, the particle size D50 of the aluminum powder may be 3 μm to 5 μm. For example, the particle size D50 of the aluminum powder may be 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or any value satisfying the above range.

[0084] (2) A coating is formed on the surface of the substrate.

[0085] In an embodiment of the present invention, the slurry obtained in step (1) is coated on at least one surface of a substrate to form a coating on the surface of the substrate.

[0086] In some embodiments of the present invention, a transfer coating machine is used to evenly coat the slurry on the opposite sides of the substrate with a thickness of 10 μm to 50 μm, and the coating thickness on one side is controlled at 45 μm to 200 μm. The thickness of the substrate provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 10 μm to 25 μm, or 25 μm to 50 μm, and so on. The thickness of the substrate provided by the present invention can also be one of 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, or any value that satisfies the above range value. The coating thickness on one side provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 45 μm to 60 μm, 60 μm to 75 μm, 75 μm to 100 μm, or 100 μm to 200 μm, and so on. The thickness of the substrate provided by the present invention can also be 45μm, 50μm, 55μm, 60μm, 65μm, 70μm, 75μm, 80μm, 85μm, 90μm, 95μm, 100μm, 105μm, 110μm, 115μm, 120μm, 125μm, 130μm, 135μm, 140μm, 145μm, 150μm, 155μm, 160μm, 165μm, 170μm, 175μm, 180μm, 185μm, 190μm, 195μm, 200μm or any value satisfying the above range.

[0087] (3) Drying treatment.

[0088] In an embodiment of the present invention, the substrate with the coating obtained after coating is subjected to a drying treatment.

[0089] In some embodiments of the present invention, the temperature of the drying process can be 30°C to 100°C. The drying temperature provided by the present invention can be a value of an interval consisting of any two values ​​in the above range, for example, it can be 30°C to 60°C, or 60°C to 100°C, and so on. The drying temperature provided by the present invention can also be one of 30°C, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C, 100°C, or any value that meets the above range.

[0090] In some embodiments of the present invention, the drying time can be 1 min to 30 min. The drying time provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 1 min to 10 min, 10 min to 20 min, 20 min to 30 min, and so on. The drying time provided by the present invention can also be one of 1 min, 5 min, 10 min, 15 min, 20 min, 25 min, 30 min or any value that meets the above range.

[0091] (4) Pulling and straightening treatment.

[0092] In an embodiment of the present invention, the tension-leveling process comprises passing the foil roll obtained after the drying process through a roller at a uniform speed under the tension of the roller.

[0093] In some embodiments of the present invention, the diameter of the roller is 3 mm to 20 mm. The diameter of the roller provided by the present invention can be a value in the interval formed by any two values ​​in the above range, such as 3 mm to 10 mm, 10 mm to 15 mm, 15 mm to 20 mm, and so on. For example, the diameter of the roller can be one of 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm, 15 mm, 16 mm, 17 mm, 18 mm, 19 mm, 20 mm, or any value that meets the above range.

[0094] In some embodiments of the present invention, the tension of the roller is 5kg to 50kg. For example, the tension of the roller can be one of 5kg, 10kg, 15kg, 20kg, 25kg, 30kg, 35kg, 40kg, 45kg, 50kg or any value within the above range.

[0095] In some embodiments of the present invention, the number of passes may be 1 to 5 times. The number of passes for foil rolls of different thicknesses may be different. An appropriate number of passes may be selected according to actual needs. For example, the number of passes may be 1, 2, 3, 4 or 5 times, without specific limitation.

[0096] In some embodiments of the present invention, the angle of the foil roll when passing through the roller is 90° to 180°, for example, the angle can be one of 90°, 100°, 110°, 120°, 130°, 140°, 150°, 160°, 170°, 180° or any value satisfying the above range.

[0097] In some embodiments of the present invention, the foil roll is moved at a constant speed through a metal rod with a diameter of 3 mm to 20 mm at an angle of 90° to 180° and a tension of 5 kg to 50 kg. The number of times foil rolls of different thicknesses pass through the metal rod may vary, and the number of times may be 1 to 5 times.

[0098] (5) Sintering treatment.

[0099] In an embodiment of the present invention, the foil coil after the tension-leveling process is sintered.

[0100] In some embodiments of the present invention, the temperature of the sintering treatment may be 560°C to 650°C. The temperature of the sintering treatment provided by the present invention may be a value in the interval composed of any two values ​​in the above range, for example, it may be 560°C to 600°C, or 600°C to 650°C, and so on. The temperature of the sintering treatment provided by the present invention may also be one of 560°C, 570°C, 580°C, 590°C, 600°C, 610°C, 620°C, 630°C, 640°C, 650°C, or any value satisfying the above range.

[0101] In some embodiments of the present invention, the sintering time can be 2h to 20h. The sintering time provided by the present invention can be a value of an interval composed of any two values ​​in the above interval, such as 2h to 10h, or 10h to 20h, and so on. The sintering time provided by the present invention can also be one of 2h, 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h or any value that meets the above range.

[0102] The present invention also provides an aluminum electrolytic capacitor, which includes the above-mentioned laminated foil for aluminum electrolytic capacitor or the laminated foil for aluminum electrolytic capacitor prepared by the above-mentioned preparation method.

[0103] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The experimental reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used in the following examples, etc., can all be purchased on the market or can be obtained by existing methods; the amounts of the experimental reagents, unless otherwise specified, are the amounts of reagents used in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods.

[0104] Example 1

[0105] A laminated foil for an aluminum electrolytic capacitor and a preparation method thereof, wherein the preparation method of the laminated foil is as follows:

[0106] (1) Preparation of slurry using aluminum powder as raw material

[0107] Aluminum powder with a particle size D50 of 4 μm is added to a mixed glue formed by epoxy resin colloid (15% by mass, solvent is ethanol) and polyurethane colloid (20% by mass, solvent is ethanol), wherein the mass of the mixed glue is 10% of the mass of the aluminum powder. The mixture is evenly mixed to obtain a slurry.

[0108] (2) Formation of coating on substrate surface

[0109] The slurry was evenly coated on the opposite two surfaces of an aluminum foil with a thickness of 30 μm, and the single-side coating thickness was controlled to be 60 μm.

[0110] (3) Drying

[0111] The obtained substrate with coating was dried at 100° C. for 3 min.

[0112] (4) Straightening treatment

[0113] The foil roll obtained after drying was moved at a constant speed on a 10 mm metal rod at an angle of 130° and under a tension of 40 kg. This process was repeated twice.

[0114] (5) Sintering treatment

[0115] The foil coil after the tension and straightening treatment is sintered at a temperature of 590° C. for 10 hours.

[0116] The sintered foil roll was sampled and punched into 1 cm × 5 cm specimens using an aluminum foil punching machine, and the performance of the specimens was tested using a bending machine.

[0117] Example 2

[0118] A laminated foil for an aluminum electrolytic capacitor and a preparation method thereof, wherein the preparation method of the laminated foil is as follows:

[0119] (1) Preparation of slurry using aluminum powder as raw material

[0120] Aluminum powder with a particle size D50 of 4 μm is added to a mixed glue of acrylic resin colloid (15% by mass, solvent is ethanol) and phthalic anhydride (20% by mass, solvent is ethanol), wherein the mass of the mixed glue is 10% of the mass of the aluminum powder, and mixed evenly to obtain a slurry.

[0121] (2) Formation of coating on substrate surface

[0122] The slurry was evenly coated on the opposite two surfaces of an aluminum foil with a thickness of 30 μm, and the single-side coating thickness was controlled to be 60 μm.

[0123] (3) Drying

[0124] The obtained substrate with coating was dried at 100° C. for 3 min.

[0125] (4) Straightening treatment

[0126] The dried foil roll was moved at a constant speed on a 10 mm metal rod at an angle of 130° and under a tension of 40 kg. This process was repeated twice.

[0127] (5) Sintering treatment

[0128] The foil coil after the tension and straightening treatment is sintered at a temperature of 600° C. for 15 hours.

[0129] The sintered foil roll was sampled and punched into 1 cm × 5 cm samples using an aluminum foil punching machine, and the performance of the samples was tested.

[0130] Comparative Example 1

[0131] The remaining operations are the same as those in Example 1, except that the foil coil after drying is directly sintered, and then straightened.

[0132] The processed foil rolls were sampled and punched into 1 cm×5 cm specimens using an aluminum foil punching machine, and the performance of the specimens was tested.

[0133] Performance Testing

[0134] The stamped samples are subjected to bending test using a bending machine, and the test pass standard is ≥130 times.

[0135] Table 1 Bending properties of laminated foils for aluminum electrolytic capacitors prepared in Examples and Comparative Examples

[0136] Group Head left (back) Head (back) Head and tail (back) Tail left (back) In the end (return) tail right (back) Example 1 161 164 164 160 164 164 Example 2 144 143 140 141 142 146 Comparative Example 1 61 59 63 60 63 61

[0137] Combination Figures 2 to 4 As can be seen from Table 1, compared with Comparative Example 1, the bending performance test of Examples 1 to 2 is improved by nearly 2 times. The cracks generated by the tensile straightening treatment before sintering in the present invention are distributed asymmetrically, such as Figure 2 As shown, the crack depth does not reach the surface of the substrate, and the stress will not be concentrated and released at one point, thereby greatly improving the bending strength of the foil roll. In comparative example 1, the cracks generated by the straightening treatment after sintering are symmetrically distributed, see Figure 4 As shown in the figure, the crack depth reaches the surface of the substrate. During the winding and cutting process, the stress on the two sides of the substrate is concentrated at the same point for release. The foil roll is prone to powdering or even breaking at this position.

[0138] The above is only a preferred specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A laminated foil for an aluminum electrolytic capacitor, characterized in that: The invention comprises a substrate and a sintered layer composed of an aluminum sintered body on at least one side surface of the substrate, wherein the sintered layer on each side has a plurality of cracks. Along the thickness direction of the sintered layer, the plurality of cracks independently extend from a surface of the sintered layer away from the substrate toward a surface of the substrate, and a depth of the crack is less than the thickness of the sintered layer.

2. The laminated foil for aluminum electrolytic capacitor according to claim 1, wherein: The substrate has the sintered layer on both sides of the opposite surfaces; Based on the substrate, the plurality of cracks in the sintered layer on both sides are independently and asymmetrically distributed.

3. The laminated foil for aluminum electrolytic capacitor according to claim 2, wherein: Based on the sintered layer on one side, the plurality of cracks are arranged at intervals along the length direction of the sintered layer; Preferably, based on the sintered layer on one side, the distance between two adjacent cracks is independently 50 μm to 350 μm; preferably 100 μm to 320 μm; Preferably, the multiple cracks of the sintered layer located at both sides are alternately distributed along the length direction of the sintered layer.

4. The laminated foil for an aluminum electrolytic capacitor according to claim 1, wherein: The width of each crack along the length direction of the sintered layer is independently 0.1 μm to 5 μm.

5. The laminated foil for aluminum electrolytic capacitor according to claim 1, wherein: The depth of the cracks is independently less than or equal to 95% of the thickness of the sintered layer; Preferably, the depth of the cracks is independently 40% to 95% of the thickness of the sintered layer; Preferably, the depth of the cracks is independently 50% to 95% of the thickness of the sintered layer.

6. The laminated foil for aluminum electrolytic capacitor according to claim 2, wherein: The thickness of the sintered layer on each side is independently 45 μm to 200 μm; Preferably, the thickness of the substrate is 10 μm to 50 μm; Preferably, the substrate is selected from aluminum foil.

7. A method for preparing a laminated foil for an aluminum electrolytic capacitor according to any one of claims 1 to 6, characterized in that: The preparation method comprises: The slurry prepared with aluminum powder as raw material is coated on at least one side of the surface of the substrate, and then drying, straightening and sintering are performed in sequence to obtain the laminated foil for aluminum electrolytic capacitors.

8. The preparation method according to claim 7, characterized in that: The tensioning and straightening treatment comprises: passing the foil roll obtained after the drying treatment through a roller at a uniform speed under the tension of the roller; Preferably, the diameter of the roller is 3 mm to 20 mm; Preferably, the tension of the roller is 5kg to 50kg; Preferably, the number of passes is 1 to 5 times; Preferably, the foil roll passes through the roller at an angle of 90° to 180°; Preferably, the temperature of the drying treatment is 30°C to 100°C, and the time of the drying treatment is 1min to 30min; Preferably, the particle size D50 of the aluminum powder is 1 μm to 10 μm.

9. The preparation method according to claim 7, characterized in that: The sintering temperature is 560° C. to 650° C., and the sintering time is 2 h to 20 h.

10. An aluminum electrolytic capacitor, characterized in that: A laminated foil for an aluminum electrolytic capacitor comprising the laminated foil for an aluminum electrolytic capacitor according to any one of claims 1 to 6 or produced by the production method according to any one of claims 7 to 9.

Citation Information

Patent Citations

  • Electrode material for aluminum electrolytic capacitor, and method for producing same

    CN103688327A

  • Electrode material for aluminum electrolytic capacitors and method for producing same

    CN111033657A

  • Method for improving brittleness of low-voltage anode foil and prepared low-voltage anode foil

    CN113470976A

  • Electrode structure body and fabrication method thereof

    CN113557583A

  • Aluminum electrode foil and preparation method and application thereof

    CN115116753A